Efficacy of serum chitotriosidase activity in early treatment of patients with active tuberculosis and a negative sputum smear - Tasci C; Tapan S; Ozkaya S; Demirer E; Deniz O; Balkan A; Ozkan M; Inan I; Kurt I; Bilgic H (Dove Medical Press, 2012)
Canturk Tasci,1 Serkan Tapan,2 Sevket Ozkaya,3 Ersin Demirer,4 Omer Deniz,1 Arzu Balkan,1 Metin Ozkan,1 Ilker Inan,1 Ismail Kurt,2 Hayati Bilgic11Department of Pulmonary Diseases, 2Department of Biochemistry, Gulhane Medical Faculty, Ankara, 3Department of Pulmonary Medicine, Dr Suat Seren Education and Research Hospital for Chest Diseases and Thoracic Surgery, Izmir, 4Istanbul Gulhane Medical Faculty, Department of Pulmonary Diseases, Istanbul, TurkeyBackground: The results of sputum culture for Mycobacterium tuberculosis must be awaited in most cases, which delays the start of treatment in patients with sputum smear-negative pulmonary tuberculosis. We investigated whether plasma chitotriosidase activity is a strong marker for early diagnosis of tuberculosis in patients for whom a bacillus smear is negative and tuberculosis culture is positive.Methods: Clinical, radiological, and laboratory features were evaluated in 75 patients, 17 of whom were diagnosed as having active tuberculosis by negative acid-fast bacillus smear and positive culture, 38 as having sequel tuberculosis which was radiologically and microbiologically negative, and 20 who served as healthy controls. Serum chitotriosidase activity levels were measured in both cases and controls.Results: The mean age of the cases with active pulmonary tuberculosis, cases with sequel lesions, and controls was 23 ± 2.4 years, 22 ± 1.7 years, and 24 ± 2.1 years, respectively. Serum chitotriosidase levels were 68.05 ± 72.61 nmol/hour/mL in smear-negative, culture-positive pulmonary tuberculosis cases (Group A) and 29.73 ± 20.55 nmol/hour/mL in smear-negative, culture-negative sequel pulmonary tuberculosis cases (Group B). Serum chitotriosidase levels from patients in Group A were significantly higher than in Group B and Group C. There was no statistically significant difference in serum chitotriosidase levels between cases with sequel pulmonary tuberculosis (Group B, smear-negative, culture-negative) and healthy controls (Group C).Conclusion: In patients with active tuberculosis and a negative sputum smear for acid-fast bacillus, plasma chitotriosidase activity seems to be a strong marker for diagnosis of active disease which can be used while awaiting culture results.Keywords: pulmonary tuberculosis, serum chitotriosidase, diagnosis, antituberculous treatment, disease activity